STRATEGI KOMUNIKASI POLITIK DALAM PEMILIHAN KEPALA DAERAH KABUPATEN KEPAHIANG 2015 - Amansyah Amansyah (JURNAL ILMIAH SYI'AR, 2018)
The election of the District Head and Deputy Regent of Kepahiang in 2015 is a decisive democratic process for 5 years. With the election, electing executive officials, namely the Regent and his Deputy in accordance with the rules of the General Election Commission (KPU) No. 7 of 2006. The dynamics of local politics ahead of The election of leader of Kepahiang was increasingly lively approaching election day. The local pair election appeared on the surface, marked by various kinds of political maneuvers carried out by each pair of the election in Kepahiang held on December 9, 2015. The pair of candidates in the 2015 in Kepahiang regency included: the first sequence number was the first pair, Ir. Firdaus Djalani and Bahruddin. Secondly, Dr. Ir. Hidayatullah Sjahid, MM and Netti Herawati, S. Sos and third Bambang Sugianto, SH, M. Hum and Arbi, S.IP. The nomination of the pair Hidayatullah Sjahid and Netti Herawati was carried out by 3 political parties who had seats in the House of Representative (DPRD) of Kepahiang regency. The parties that carry the pair Hidayatullah Sjahid and Netti Herawati include: Nasdem Party, Hanura Party, Gerindra Party. The nomination has been supported by parliamentary parties and non-parliamentary parties in general through three important stages, namely, first, the selection of candidates. Second, filtering and selection that has been netted. Third, the determination of candidates. Political Communication Strategy of Hidayatullah Sjahid and Netti Herawati pairs. Previously, he was also the acting officer (PLT) of the regent in Kepahiang. As a candidate who has held office, Hidayatullah Sjahid's position has a number of advantages over other candidates in the 2015 Kepahiang Regional Election. Besides having political investment in the Kepahiang regional election, Hidayatulah Sjahid as a candidate who has benefited from cooperating with Netti Herawati, who has high popularity in people's eyes.